2021
DOI: 10.1038/s41398-021-01366-y
|View full text |Cite
|
Sign up to set email alerts
|

Brain markers predicting response to cognitive‐behavioral therapy for social anxiety disorder: an independent replication of Whitfield-Gabrieli et al. 2015

Abstract: Predictive brain markers promise a number of important scientific, clinical, and societal applications. Over 600 predictive brain markers have been described in published reports, but very few have been tested in independent replication attempts. Here, we conducted an independent replication of a previously published marker predicting treatment response to cognitive-behavioral therapy for social anxiety disorder from patterns of resting-state fMRI amygdala connectivity1. The replication attempt was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Harris et al ( 196 ), showed that treatment with pregabalin but not placebo altered insula chemistry and connectivity in patients with fibromyalgia but neither treatment was accompanied by a significant change in clinical pain rating. Most recently, Ashar et al used fMRI as “an objective correlate of treatment effects” in a clinical trial (NCT0394148) testing pain reprocessing therapy vs. placebo in patients with CLBP ( 197 ) and reported decreased anterior middle cingulate cortex activity in response to evoked clinical pain and increased anterior insula to somatosensory cortex connectivity with pain reprocessing therapy more than with placebo treatment. In addition, Reckzeigel et al ( 198 ) recently used brain biomarkers to assess the risk of transition from sub-acute to chronic pain in sub-acute low-back pain patients entering a pharmacological clinical trial (NCT01951105) aimed at preventing the transition to CLBP.…”
Section: Methods Of Detection and Clinical Context Of Usementioning
confidence: 99%
“…Harris et al ( 196 ), showed that treatment with pregabalin but not placebo altered insula chemistry and connectivity in patients with fibromyalgia but neither treatment was accompanied by a significant change in clinical pain rating. Most recently, Ashar et al used fMRI as “an objective correlate of treatment effects” in a clinical trial (NCT0394148) testing pain reprocessing therapy vs. placebo in patients with CLBP ( 197 ) and reported decreased anterior middle cingulate cortex activity in response to evoked clinical pain and increased anterior insula to somatosensory cortex connectivity with pain reprocessing therapy more than with placebo treatment. In addition, Reckzeigel et al ( 198 ) recently used brain biomarkers to assess the risk of transition from sub-acute to chronic pain in sub-acute low-back pain patients entering a pharmacological clinical trial (NCT01951105) aimed at preventing the transition to CLBP.…”
Section: Methods Of Detection and Clinical Context Of Usementioning
confidence: 99%
“…Santos et al ., 2019 ; Fig. 1C ), this method also demonstrates low replicability (Ashar et al ., 2021 ) reflecting issues concerning the reliability of fMRI measures (Noble et al ., 2019 ) and the heterogeneity of mental health disorders (Forbes et al ., 2023 ). As one example, significant within-group differences observed in precuneus and amygdala rsFC among individuals with SAD, in the absence of any group-level difference with healthy controls (Mizzi et al ., 2024 ), further necessitates an approach accounting for patient heterogeneity when employing a predictive (neural) model (Talmon et al ., 2021 ).…”
Section: Understanding Sad With Neuroimaging and Computational Datamentioning
confidence: 99%
“…Although promising results exist, CPM is still understudied, as is rsFC for anxiety disorders more broadly (Zugman et al 2023). Only two studies used rsFC analyzed with methods different from CPM, to predict treatment outcome in anxiety (Whitfield-Gabrieli et al 2016; Ashar et al 2021). Both studies examined adults, and the predictive model failed to replicate.…”
Section: Introductionmentioning
confidence: 99%